Preformed portals facilitate dendritic cell entry into afferent lymphatic vessels - Pflicke, Holger (The Rockefeller University Press, 2009)
Although both processes occur at similar rates, leukocyte extravasation from the blood circulation is well investigated, whereas intravasation into lymphatic vessels has hardly been studied. In contrast to a common assumption—that intra- and extravasation follow similar molecular principles—we previously showed that lymphatic entry of dendritic cells (DCs) does not require integrin-mediated adhesive interactions. In this study, we demonstrate that DC-entry is also independent of pericellular proteolysis, raising the question of whether lymphatic vessels offer preexisting entry routes. We find that the perilymphatic basement membrane of initial lymphatic vessels is discontinuous and therefore leaves gaps for entering cells. Using a newly developed in situ live cell imaging approach that allows us to dynamically visualize the cells and their extracellular environment, we demonstrate that DCs enter through these discontinuities, which are transiently mechanically dilated by the passaging cells. We further show that penetration of the underlying lymphatic endothelial layer occurs through flap valves lacking continuous intercellular junctions. Together, we demonstrate free cellular communication between interstitium and lymphatic lumen.